Effect Of Maintenance System And Simulator Pilots On Aviation Safety In Airlines. (July 2020) - Rahmawati, S. D.; Maulida, S. J. R.; Rafi, S.; Ratnasari, Devi
Abstract: Safety and security are a priority in an aviation industry that is very mindful because it is crucial. In order to achieve that virtue, there are some things that must be noticed by the airline in supporting safety and security is the maintenance system which pays attention to the profanation of an aircraft to operate and A pilot simulator to prepare physical and mental pilot readiness in all natural situations and conditions while minimizing the risk of falling planes, two factors affecting the pilot's performance in operating the aircraft Will reduce the accident rate significantly and can improve the pilot's ability to deal with problems in the field through certain simulations related to these problems. This research aims to study flight readiness in terms of feasibility control by maintenance system and pilot readiness in the face of emergencies and decision making in crucial situation. This research uses a regression method whereby the data retrieval technique uses the questionnaire with the target of the pilot respondent of the airline Garuda Indonesia. The result of analysis Acquired linear equation multiple regression Y = 0.754+0.383X1+0.398X2, R is obtained at 0.518.